(L' Herit) (Phytolaccaceae) Methanol Root Extract Protects Liver from Acetaminophen-Induced Injury in Rats - Gudeta Duga Geresu MSc; Tilahun Tesfaye Abebe MSc; Diriba Alemayehu Gadisa MSc; Getu Melese Taye MSc; Dejene Hailu Bedada MSc; Tamirat Bekele Baressa MSc; Shemsu Umer Hussen PhD; Tesemma Sileshi Chala PhD (SAGE Publishing, 2024)
Phytolacca dodecandra (L' Herit), or 'Endod', is one of the widely known medicinal plants in Ethiopia. Berries of the endod have been used as a detergent for centuries. The present study was aimed to test the hepatoprotective effects of the plant against acetaminophen (APAP)-induced liver injury in rats. Mice of either sex were used for oral acute toxicity tests and APAP-induced lethality tests. Hepatoprotective experiments were done on male rats using 2 g/kg of APAP to induce liver damage. Liver enzymes, total bilirubin (TB), and lipid profile were determined. Liver tissues were also examined histopathologically to see a morphologic change in the control and experiment groups. The protective effect of the plant extract was also tested through sodium pentobarbital (SPB)-induced sleeping time. A significant increase in serum levels of liver enzymes, TB, low-density lipoprotein (LDL), and triglycerides (TGs) was seen from oral administration of 2 g/kg APAP. Total cholesterol (TC) and high-density lipoprotein (HDL) levels were decreased. Serum levels of all parameters were reversed to normal after administration of silymarin 100 mg/kg and, 100, 200, and 400 mg/kg doses of the extract. A significant dose-dependent hepatoprotective effect of Phytolacca dodecandra Methanol Root Extract (PDME) was seen in terms of LDL. Histopathological investigations and SPB-induced sleeping time confirmed the findings of biochemical analysis. The findings of the present study indicate that PDME protected the liver from APAP injury.